The Design of Medical Waste Treatment in Public Health Center (MWT-P) for Reducing Total Bacteria Count in Banjarbaru - M. Irfa'i; Arifin Arifin; Ferry Kriswandana; Imam Thohari (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: The increase in medical waste in health service facilities in Indonesia is linearly consistent. The quantity of medical waste that causes a complex problem is a high cost of processing clinical waste. Legislation requires medical or clinical waste to be processed not to cause nosocomial and other environmental pollution. Medical or clinical waste treatment requires excessive technology and very high processing expenses. Processing medical waste requires innovation in processing medical waste to be applied easily in health care facilities (Public Health Center). Method: This research was conducted by simulating variations in the stages of processing medical waste used to be the Experiment Pre and Post Test only without Control Group design. Simulation variations used include contact time Chlorine (5 minutes, 10 minutes) and Chlorine Dose Variation (25 ppm, 50 ppm). This research was conducted in the Public Health Center of the City of Banjarbaru in 2018. Result and Discussion: The content of bacteriological numbers in medical waste before processing is, on average, 1,973 MPN / 100 ml; after being treated with MWT-P, the bacteria is reduced to 4 MPN/100 ml. The content of the liquid waste bacterial number of the final processing decreases to 0 MPN/100 ml. Conclusion: The study results concluded that the use of MWT-P decreases the quantity of medic or clinical waste microorganisms or bacteria. The final waste processing with MWT-P resulted in the number of medical waste bacteria in the treatment reaching zero. MWT-P is a low cost and easy to perform medical or clinical waste management tool. MWT-P is a stage of the B3 waste management framework, especially medical waste, in health care facilities.